Enunciados em provas de língua portuguesa: um foco nas respostas e nas estrategias de leitura dos alunos - Rosangela Maria da Cruz (2012)
This research verifies how students from the last year of the elementary school comprehend utterances of Portuguese tests through answers analysis which are written to the questions. The corpus of this qualitative research is constituted of utterances of Portuguese text comprehension, the answers produced by the students to these same utterances and semi-structured interviews with students and with the teacher of one class. We intend to understand which skills are triggered / used, based on utterance analysis of two Portuguese tests done by the students and their answers to these tests. We have adopted Kleiman (2004), Koch and Elias (2008) reading conceptions. These authors consider reading as a meaning construction activity, which presumes an author-text-reader interaction. In this activity, besides the suggestions and signs offered by the text, the reader previous knowledge is also involved in this happening. Reading involves, therefore, the readers active stance which implies an activation of his / her cognitive structures and previous knowledge as well; it also depends on the discursive situation in which the reader finds him / herself in the reading moment. In this perspective, utterances and their answers are treated like texts. While texts (empirically configured in determined compositions), will also be seen like genres, due to the fact that they are models relatively stable which configure themselves in a determined language use social sphere (BAKHTIN, 2003). So the genre is conditioned to a textual scheme which brings many formal and functional consequences. Utterances were analyzed according to Moretto (2005) categories about traditional and operative tests and the questions typologies as well, developed by Marcuschi (2003). Results which refer to utterances analysis sign that those which have more issues, considering comprehension are those which have an incomplete or inadequate formulation. In this analysis, we could see that students have more correct answers when content anticipation or prediction skills, texts properties anticipations, comparison of information and development of local inferences are evaluated. In the other hand, students have more wrong answers when in the utterances are predicted skills such as: world knowledge activation, global inferences development and metalinguistic thinking. Test answers and interviews with the teacher and with students revealed the other side of the situation: students present more mistakes due to minimum, improper and with several set of issues comprehension levels.